Administrative The Impact of The Covid-19 Pandemic on Administrative Law Policies and Practices in Indonesia: A Review of Constitutional Governance and Administrative Reform - Bambang Sumeidi (Dinasti Research, 2026)
The COVID-19 pandemic has prompted the Indonesian government to enact various emergency measures that have significantly impacted the practice of Administrative Law. Under these circumstances, the government is required to act swiftly while upholding the principles of the rule of law, particularly legality, accountability, and constitutionality. This study aims to analyze the implementation of emergency policies from an Administrative Law perspective, particularly regarding legality, administrative discretion, and public policy accountability. The method used is normative legal analysis employing legislative, conceptual, and comparative approaches. The research findings indicate that emergency policies are not yet fully consistent with the principles of administrative law. The study identified regulatory inconsistencies, an expansion of discretionary power without adequate oversight, and a lack of policy transparency. Furthermore, emergency policies also face challenges in maintaining a balance between effectiveness and constitutional compliance. This study concludes that there is a need to strengthen the principle of legality, limit discretion, enhance accountability, and strengthen constitutional oversight to achieve good governance